Hubungan Antara Minat Belajar Dengan Hasil Belajar Matematika di Sekolah Dasar - Pertiwi, Sisvi Gusva; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to determine the relationship between interest in learning with student mathematics learning outcomes in class IV SDN Cluster-II Ampek Angkek District Agam Regency. This type of research is correlational research using a quantitative approach. The sample of this study was all students of class IV SDN 15 Ampang Gadang, Ampek Angkek District, Agam Regency as many as 30 students. The results of research data calculations using the Product Moment formula with the acquisition r count of 0.4145 is greater than the r table with the dedree of freedom (df) 28 of 0.361 at a significance level of 0.05 (5%) and the r count of 0.4145 lies at (≥0.40 - <0.70) which means that Ho is rejected and Ha is accepted, so the hypothesis shows a significant relationship between Learning Interest with Mathematics Learning Outcomes of Grade IV students of Elementary Schools in Cluster II, Ampek Angkek District.